MEMBRANE FILTRATION TECHNOLOGY FOR WATER TREATMENT IN TERMS OF MEMBRANE PERFORMANCE, ENERGY CONSUMPTION, AND COST ASPECTS: A REVIEW - Firdaus Firdaus; Eli Trisnowati; Fatiatun Fatiatun (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
The problems of water quality and its management are a global issue that must be resolved. Technology of membrane filtration shows the good potential of water treatment to improve water quality, eliminate harmful contaminants and efficiently restore nutrients. This article aims to give a comprehensive review of membrane filtration, consists of membrane filtration performance to remove contaminants, energy consumption, cost aspects and strategies of antifouling. Technologies in membrane filtration are microfiltration (MF), ultrafiltration (UF), nanofiltration (NF) and (reverse osmosis) RO. The results of this study indicate that, MF/UF system can effectively remove bacteria and be used as a pre-treatment before the NF/RO process. NF/RO system can remove contaminants higher than MF/UF. It can remove almost all contaminants, ions, heavy metals, viruses and pharmaceutical compounds (PhAC). However, the system is more susceptible to membrane fouling, but these problems can be solved with adequate pre-treatment. Water treatment with NF and RO offers a good alternative because its operation makes it possible to use lower energy consumption compared to conventional water treatment. Based on the cost aspect, if the virus and ion contamination are not the main target in the filtering and not for consumption, the MF/UF system is sufficient and will be more economical than using NF/RO. The finding of this study can provide insight into the effectiveness of membrane filtration technology in water treatment. Future research can develop membrane filtration technology so that it has good performance, low energy consumption and low cost.